On the question of the axiology of the image of man in the epic «Dzhangar» - V. Yangindulam (Nomadic Civilization: Historical Research)
Jangar Tuul is a unique cultural heritage that preserves the history, worship and values of early Mongolians. The oral literature and language of any people can inform the culture and express the cultural similarities and differences of the ethnic groups. In Jangar epic, the warrior hero not only wins the competition with his strength, wisdom and knowledge, but also wins because he was born with more virtues. In the example of the Jangar poem, it was clarified that there was a form of appreciation among the Mongolians, who evaluated people based on their virtues given by heaven. Only those with a strong will can win. After all, they are stubborn to achieve their goals, obstacles and doubts cannot break them. They have a strong character, a will to win, and self- confidence. There are such warriors in epics. These are real heroes. The epic gives us vivid examples of endurance and selfless courage. We learn from heroes not to give up in difficult life situations.